The Process Of Investigation Against The Criminal Action Of Narcotics - Andriawan, Ferry; Maerani, Ira Alia; Sulchan, Achmad (Law Development Journal, 2021)
The purpose of this study is to find out the process of investigating narcotics criminals at the Pekalongan Police and to find out the obstacles and solutions faced in the process of investigating narcotics criminals at the Pekalongan Police. The type of research used in this research is normative empirical, which begins deductively with an analysis of the articles in the relevant laws and regulations. The problems examined in this study revolve around legislation and relate to their application in practice. Research results Pekalongan Resort Police The process of carrying out investigations against narcotics perpetrators is in accordance with the provisions of the Criminal Procedure Code, the obstacles are the network of narcotics abuse crimes which are easily broken in the chain, transportation facilities for investigators of the Pekalongan Police Narcotics Unit are felt to be a bit hampering, and solutions with pre-emptive efforts (coaching) and Preventive (prevention).